Systemic delivery of aptamer–drug conjugates for cancer therapy using enzymatically generated self-assembled DNA nanoparticles. Issue 45 (14th November 2020) - Tran, Binh Thanh; Kim, Junghyun; Ahn, Dae-Ro
Abstract : Aptamer–drug conjugates (ApDCs) are promising anticancer therapeutics with cancer cell specificity. Abstract : Aptamer–drug conjugates (ApDCs) are promising anticancer therapeutics with cancer cell specificity. However, versatile in vivo applications of ApDCs are hampered by their limited serum stability and inability to reach the tumour upon systemic administration. Here, we describe DNA nanoparticles of ApDCs as a platform for tumour-targeted systemic delivery of ApDCs. DNA nanoparticles of approximately 75 nm size were fabricated by self-assembly of a polymerised floxuridine (FUdR)-incorporated AS1411 aptamer produced via rolling circle amplification. The DNA nanoparticles of ApDCs showed highly efficient cancer cell uptake, enhanced serum stability, and tumour-targeted accumulation. These properties could be successfully utilised for tumour-specific apoptotic damage by ApDCs, leading to significant suppression of tumour growth without considerable systemic toxicity. Molecular analysis revealed that the enhanced anticancer potency was due to the synergic effect induced by the simultaneous activation of p53 by AS1411 and the inhibition of thymidylate synthase by FUdR, respectively, both of which were generated from the DNA nanoparticles. We therefore expect that the DNA nanoparticles of ApDCs can be a promising platform for tumour-targeted delivery of various nucleoside-incorporated ApDCs to treat cancer.